Seizure - Reichs, Kathy (LONDON William Heinemann, 2011)
The Virals' home on Loggerhead Island is under threat and only one thing can save it: a lot of money. Rumour has it that notorious pirate Anne Bonny hid her treasure somewhere in Charleston in 1720. No one knows where, but Tory Brennan is certain that the Virals can work out Bonny's cryptic clues.
Keywords: Treasure troves -- South Carolina--Charleston -- Viruses